The historical and contemporary knowledge on the elasmobranchs of Cananeia and adjacent waters, a coastal marine hotspot of southeastern Brazil - Santos, Paulo R.S. [UNESP]; Balanin, Samuel; Gadig, Otto B.F. [UNESP]; Garrone-Neto, Domingos [UNESP] (Elsevier, 2022)
In this study we present data on the richness of sharks and rays from the southern coast of São Paulo, southeastern Brazil, in a coastal area considered as an essential habitat for many species of elasmobranchs. Based on information produced between the 1950s and 1970s, we constructed a historical timeline about the knowledge of sharks and rays as well an updated and annotated list of elasmobranchs for Cananeia and adjacent waters, comparing the local richness with data from other areas. A total of 62 species (36 sharks and 26 rays) were recorded, which represent 68.1% of the species previously known to occur along the entire State of São Paulo and about 33.3% of the total richness known for marine elasmobranchs in Brazil. Problems related to a low number of peer-reviewed publications and a low taxonomic resolution of records in official fisheries databases since the end of the 1970s reflected a historical problem related to fisheries management of elasmobranchs in Brazil. Thus, a long-term monitoring that refines the categories of elasmobranchs landed is suggested for the proper orderly management of the fishing activity in an area that represents a hotspot for this group in the subtropical Southwestern Atlantic.
Keywords: Elasmobranchs; Fauna; Fisheries monitoring; History; Victor Sadowsky